Motorcycle/Donorcycle: Improving Motorcyclist Safety in Győr, Hungary - Brant von Goble (Engineering Proceedings)
Due to their high fatality rate, motorcycles, often referred to as “donorcycles” in the U.S., present unique safety challenges. In Hungary, motorcycle safety remains a critical issue despite a relatively low per capita rate of motor vehicle deaths, largely due to limited ownership and recognition. This study examines historical trends in motorcycle use in Hungary and the economic factors influencing their current prevalence. By emphasizing the crucial role of helmets and safety gear, road conditions, and environmental factors, this paper provides actionable recommendations to improve motorcycle safety in Győr and the surrounding regions. Implementing these recommendations stands to significantly reduce accidents and save lives, ensuring safer roads for all.